Input–Output Matrix study: A theoretical frame to study the impact of Brazilian IPI reduction in final demand - Rodrigo Emmanuel Santana Borges (EconomiA, 2014)
The economic crisis of 2008–2009 will be known as the day when the creator knelt before its creation (Syll, 2010). Amid such economic mess created by economists (and so-called engineers) themselves, there seems to be a single economic perspective: every man for himself and save yourself if you can. In the midst of this major disruption in the global economy, the Brazilian government decided, in a set of economic measures, to promote a partial and time-limited VAT reduction as its main countercyclical policy. This paper proposes to measure which were the direct and indirect effects of lowering the taxes for a limited time on production, employment generation and income. Additionally, it intends to check whether the reduction on IPI level, a tax that is one of the VATs in Brazil, was indeed the most efficient choice among the other value added taxes in Brazil. In order to accomplish such objectives, a simple final demand model for the GDP is adopted, and the latest national accounts input–output data is taken as a basis to infer the multipliers for the variables chosen and to estimate hypothetical impacts of reduction in other taxes instead of IPI reduction in the specific sector. Currently, the consensus is that the countercyclical economic policy adopted in Brazil had a positive result and fulfilled the expected goals.